RELATIONSHIP OF PATIENT SAFETY CLIMATE TO THE IMPLEMENTATION OF PATIENT SAFETY TARGETS IN THE INTEGRATION CLINIC OF RSIGM SULTAN AGUNG SEMARANG - Adetiya Denti Wijaya Kusumaningtyas; Kusuma Arbianti; Moh Husnun Niam (Jurnal Medali, 2022)
Background: Patient safety is an important issue for the health care system in Indonesia. Patient safety management is an attempt to save all medical personnel by reducing and minimizing medical injuries that may occur to patients. One of these efforts is the implementation of a patient safety climate. Patients safety climate is a perception of group members about procedures, practices, and types of behavior towards patient safety. A high patient safety climate it will increase the implementation of patient safety goals which will affect a patient safety incident. Methods: Using an observational analytical research method with a cross sectional research design by distributing questionnaires to 70 young dentists at the integration clinic of RSIGM Sultan Agung Semarang. The questionnaire used in this study was the safety attitude questionnaire and the patient safety target implementation questionnaire which have been tested validity and reliability test. The research data were processed using the Spearman test.Results: there is a significant relationship between the patients safety climate and the implementation of patient safety goals p<0.05, the better the patients safety climate is the more the implementation of patient safety goals will decrease which will reduce a patient safety incident. Conclusion: It can be concluded there is a relationship between the patient safety climate and the implementation of patient’s safety goals with data p-value of 0.001, the correlation coefficient is 0.402 that the close relationship between the two variables is categorized as moderate with a positive correlation direction.